STRATEGI PENGEMBANGAN SUMBERDAYA MANUSIA DI ERA PERSAINGAN INDUSTRI MEDIA - Saniyah, Salsabillah Putri; Kurniawati, Desi Tri (Jurnal Kewirausahaan dan Inovasi, 2022)
The competition in the media industry in the digital disruptive era is getting tougher, including KG Media as one of the players in the media industry that is quite calculated. Therefore, human resources are needed who have technical skills, human skills, and managerial skills. This can be done through continuous training. This research is a qualitative research with a descriptive approach that aims to analyze the employee development program implemented by KG Media. Collecting data from this study using observation and documentation techniques. The results of this study indicate that the development of human resources at KG Media in the "future program for business development" program has been designed comprehensively, coherently and has a strong scientific basis, starting from the planning stage to evaluation. The program has been running well and in accordance with the training needs of employees, this is based on the evaluation of the implementation of the program which shows that the attendance rate of participants is high, the material is relevant and there is a strong desire to attend further training. The results of this study contribute to the importance of training programs for human resource development in the media industry.